Forty-Seven Years of Environmental Management Accounting Research: A Bibliometric Analysis - DB, Chetanraj; JP, Senthil Kumar (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).05, 2023)
Environmental sustainability is considered as responsible engagement with the environment in order to prevent the depletion or degradation of natural resources and ensure long-term environmental quality. Environmental management accounting (EMA) is a tool that aids in enhancing environmental performance and environmental information management. EMA is a growing topic, but there hasn't been a complete analysis to pull everything together and make sense of it all. By adopting bibliometric review, through performance analysis, and science mapping, our research fills in this research gap. Biblioshiny in R and VOS viewer is used for conducting data analysis. Through an extensive study of 1,075 documents, this study discloses the publication and citation trend, top influential authors, journals, publications, and top productive institutions and countries. The study also identifies topic trends through temporal analysis. Different thematic clusters are identified through bibliographic coupling and Co-occurrence of the author’s keywords ( i.e. Social and environmental accounting, Environmental management accounting, Environmental performance, Carbon accounting, Sustainability, and sustainable development, Eco-system services, Environmental disclosure, and corporate social responsibility). Centrality measures are presented to show the impact of the author and keywords. The study concludes with suggestions for future study, and ways forward focusing on Circular economy, green accounting, material flow cost accounting, carbon accounting, sustainability, etc. The study is wholly dependent on the Scopus database, further studies can explore other databases like Web of science, google scholar, and others.